Detection of antimicrobial-induced survival/dead bacteria via mEos4b photoconversion: a preliminary study - Yilmaz, Ilknur; Demir, Humeyra; Tureyen, Aleyna Eslem; Ozbek, Tulin (IOP Publishing Ltd, 2025)
The escalating prevalence of hospital-acquired infections poses a critical challenge for healthcaresystems worldwide. Effective management requires rapid identification of pathogens and theirantibiotic resistance profiles. In this study, we utilized the photoconvertible mEos4b protein, whichtransitions from green to redfluorescence upon blue light exposure, to distinguish live from deadbacteria. The mEos4b gene was cloned into a prokaryotic vector and expressed inEscherichia coliBL21. The Minimum Inhibitory Concentration(MIC)of the transgenic bacteria was determined forfive antibiotics, followed by a post-antibiotic effect assessment over a two-hour exposure period. Theoptimal photoconversion time for mEos4b was established as 90 s, and confocal microscopy was usedto visualize live(green)and dead(red)cells post-exposure. The mEos4b-TR system proved highlyspecific, accurately distinguishing live and dead bacteria without producing false positives, even incontrol groups, which is a common issue in commercial live-dead kits. By relying on cellular metabolicactivity rather than dyes, this system minimizes nonspecific interactions and contamination, makingit more reliable than traditional methods prone to false readings. These results highlight the potentialof the mEos4b-TR system as a superior alternative for rapid, precise bacterial viability assessments,particularly in determining antibiotic susceptibility. This preliminary study demonstrates the system'sdifferentiation of viable and non-viable cells, suggesting its potential application in future studiesinvolving novel antibacterial agents to refine antibiotic sensitivity testing.
Keywords: mEos4b; E. coli BL21; photoconversion; survival/dead; antimicrobials; FLUORESCENT PROTEINS; CHROMOPHORE; DYNAMICS; EOSFP; BLUE; Chemistry